THERAPEUTIC MANAGEMENT OF PRAVAHIKA (AMOEBIC DYSENTERY) THROUGH AYURVEDIC REGIMEN: A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2017)
Hurry, worry and curry are the three factors which causes intestinal upsets frequently and leads to gastrointestinal problems in modern life. Pravahika (Amoebic dysentery) is also one of the important and oftenly occurring Vyadhis of Annavaha and Pureeshvaha Srotasas in current time. Pravahika is the Pakwasahayagata kaphajavikara with symptoms of Sarakta mala, Sapravahana mala, Sakapha mala, Daah, Jwara, Bhrama Daurbalya, Anannabhilsha, Sweda and Trishna. A case report of a patient with a history of loose motion with mucous discharge for the 6 months visited Ayurveda OPD, is presented in this study. Routine stool examination, blood glucose, serum lipid profile and liver function test were performed. The patient was treated with Ayurvedic medicine Kutajghan vati (1 gm), Bilvadi churna with Takra (6 gm) and, Chitrakadi Gutika (250 mg) in divided doses for 1 month. The patient was followed up for every 7th day and there was significant improvement in the clinical features after 1 month of treatment with the Ayurvedic medicines. There were no side effects reported. This case study demonstrates the therapeutic efficacy of Bilvadi churna, Kutajghan vati and Chitrakadi Gutika in the rapid management of Pravahika.